If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -75x = 0 Combine like terms: 12x + -75x = -63x -63x = 0 Solving -63x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-63'. x = 0 Simplifying x = 0
| 17-2x=-6x+1 | | 8-2/3 | | 6y-7=2y+5 | | 5x+1.7=7.7 | | 5(a-6)+12=2(a-6) | | 180=x+x(5)+6 | | 6-23=6x-8-5x | | 2.3+x=0.5 | | x+(x/30/8.5*7)=10000 | | 0.4x=0.28 | | x+8(3)=x(2)-1 | | x+5/6=-1 | | 48s^2+84s=-36 | | 156/52 | | (15x+2)+(8x-5)= | | -5(-5)-4(-3)(2)= | | 6a^2-150=0 | | 0.28+3/10= | | 0.6x-0.4(16-3x)=-0.8(x-5) | | 0.6x+9.2=5.3 | | 5(-8)-4(7)= | | 4x-7x-12=3x+7-12 | | 0.28+3/10 | | 2(5+5x)=9(x-2) | | 2x-65=635 | | -2x^2+x+2=0 | | 0.2x+0.1=0.5x-0.5 | | 4(3n+5)=9(8n+4)+6 | | 10x+3=43+10x | | 18x-15=7(2x-1)+4x-8 | | 18=-6u | | 23/34+45/145= |